Predictors for oral cancer in Brazil - Isabella Lima Arrais RIBEIRO; Johnys Berton Medeiros da NÓBREGA; Ana Maria Gondim VALENÇA; Ricardo Dias de CASTRO (Universidade Estadual Paulista, 2017)
Abstract Introduction The incidence of lip, oral cavity and oropharynx cancer in Brazil is one of the highest worldwide. Objective This study aimed to identify predictors for oral cancer in Brazil between 2010 and 2013. Method Through a time series study in which 14,959 primary head and neck cancer diagnoses were evaluated. The variables of interest were gender, age, race, education level, family history of cancer, alcohol consumption, smoking, and previous cancer diagnosis. The outcome variable was divided into "oral cancer" and "cancer of other head and neck regions." The data were analysed by multiple binary logistic regression; α=5%. Result The protective factor was: approximately 12 years of education (OR = 0.85). The risk factors were: being an ex-consumer (OR=1.19) or consumer (OR=1.11) of alcohol, tobacco use (OR=1.35) and a prior diagnosis of cancer that went untreated (OR=1.21). Conclusion Was concluded that the oral cancer had the following predictors compared to other types of head and neck cancer during the same period: approximately 12 years of education (protective factor) and ex-consumer or consumer of alcohol, smoking and previous diagnosis of cancer that went untreated (risk factors).